Relationship Marketing and Digital Marketing on Competitive Advantage in Enhancing SMEs Marketing Performance at Semarang Regency - Sudari, Suci Ayu; Pambreni, Yuni (Jambura Science of Management, 2024)
Purpose: The study is conducted to analyze the effect of Relationship Marketing and Digital Marketing toward Competitive Advantage in Enhancing Marketing Performance at SMEs in Semarang Regency.Design/Methodology/Approach: The research method used path analysis. The independent variables in this study are relationship marketing and digital marketing, competitive advantage as an intervening or mediating variable, and marketing performance as the dependent variable. Primary data was obtained by questionnaire as the instrument of collecting data. The data was processed with SPSS 23. The population in this study is 11959 SMEs in Semarang Regency, then the number of samples is 100 SMEs, the sample was determined by Slovin formula.Findings: The study showed that relationship marketing and digital marketing have an effect on competitive advantage in marketing performance improvement. SMEs can increase customer trust and commitment by maintaining the quality of the products sold so that customers are not disappointed with the product when making repeat purchases. In other ways, SMEs must provide good service to customers and prospective customers. SMEs need to compile or create even more attractive promotional programs so that customers become interested in buying products at SMEs, by sharing promotions more frequently on social media so that promotional information can be reached by customers more broadly. Improving good relations with customers, one of which is always ready to be responsive in serving customers when customers need information or services from SMEs. To improve marketing performance, SMEs owners can pay more attention to their relationship with customers and the use of digital marketing in carrying out their business.